SERUM POTASSIUM LEVELS AND ELECTRCARDIOGRAPHIC STUDY IN YOUNG ALPACAS (Vicugna pacos) - Dávila F., Roberto (2014)
The aim of this study was to determine the levels of serum potassium and electrocardiographic parameters in young alpacas. Thirty alpacas (17 males and 13 females) from 1 to 60 days of age from various alpaca farms in Maranganí, Cusco were used. The levels of serum potassium was 5.91 ± 1.48 mmol/L and without statistical differences between sexes. The electrocardiographic values were: P wave time, 0.04 ± 0.0s; P wave amplitude, 0.173 ± 0.058 mV; PQ time, 0.101 ± 0.02 s; QRS time, 0.038 ± 0.006 s; QRS complex, 0.557 ± 0.412 mV; QT time, 0.237 ± 0.040 s; T wave amplitude, 0.413 ± 0.266 mV. Moreover, animals with increased T wave had potassium values above 5.5 mmol/L but without signs of heart disease. In addition, values of serum potassium and electrocardiographic paramters showed similarity to the values of other species.